Hubungan Efikasi Diri Dengan Kepatuhan Minum Obat Pada Pasien Tuberkulosis Paru Di Rumah Sakit Swasta X Kota Bekasi - R. Sapeni, Muhammad Al-Amin; Melinda, Elsa; Yuniyanti, Tri Ayu; Calvin Christo Paat, Toar; Anwar, Irawati; Nur, Rezeki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Introduction: The high number of incidents related to pulmonary TB is due to long enough treatment so that many sufferers stop taking medication before the treatment period is finished (Sukirawati, 2020). Meanwhile, the success rate for the treatment of this disease has not yet reached the national target, if you refer to the target set in the strategic planning of the Ministry of Health, which is 90%. One of the factors that support increasing medication adherence is self-efficacy. Purpose: This study aims to determine the relationship between Self-Efficacy and Adherence to Taking Medication in Pulmonary TB Patients at X Private Hospital, Bekasi City. Method: The type of research in this research wais descriptive research with a quantitative approach and with a cross sectional research design. Data collection was undertaken using the MMAS-8 questionnaire (Morisky Medication Adherence Scale-8) and the TBESES-21 questionnaire (Tuberculosis Self-Efficacy Scale) for 31 pulmonary TB patients at Private Hospital of X Bekasi. Data were analyzed using SPSS with the Fisher-Exact Test. Results: The results of this study indicated that there was a relationship between Self-Efficacy and Medication Compliance in pulmonary TB patients at Private Hospital of X Bekasi City which is indicated by a significance value (p-value) of 0.001 (α < 0.05) and it had a strong relationship indicated by a correlation coefficient of 0.540. Conclusion: Self-efficacy is related to Medication Compliance in pulmonary TB patients at Private Hospital of X Bekasi